Pradesain Mesin Cuci Mobil Semi Otomatis dengan Autodesk Inventor - Samhuddin; La Ode Ahmad Barata; Jaka Seru Dwi Saputra (Piston: Jurnal Teknologi, 2024)
A car wash is a facility used to clean the outside and inside of a car, which can be done manually and automatically. The use of an automatic system allows car washing to be faster than a manual washing system that still relies on human labor. The car washing machine pre-design article provides an overview of automatic car washing pre-design. This planning uses the Autodesk inventor application with 6061 aluminum material with a design size of 80 mm × 80 mm × 5 mm. In this plan, the planned water requirement is 300L/car, where the nozzle radius r1 = 25 mm, r2 = 10 mm, and nozzle pressure of 24,410 Pa with 24 nozzles. Electric power is used at 1310 watts where the pump pressure is 34,872 Pa. All frame loads and other supporting components were analyzed using Autodesk InventorTM software. The maximum stress and strain, deflection and safety factor of the frame were also analyzed. This article presents the design of the controller system using Arduino. The general design of the water circulation system is also shown in the design proposal of this machine.